1971
DOI: 10.1063/1.1676523
|View full text |Cite
|
Sign up to set email alerts
|

Triplet State of Benzaldehyde

Abstract: The phosphorescence spectra of benzaldehyde-h6, −1d1, −4d1, −3, 5d2 and −d6 have been studied optically in close packed matrices (acetophenone and methyl benzoate) and relaxed matrices (methylcyclohexane and perfluoro-n-hexane) at 4.2°K. All the spectra were sharp and could be analyzed vibrationally. In the close packed matrices, of the 11 possible out-of-plane (a″) fundamentals, nine are observed in Herzberg—Teller borrowing of intensity. The strongest modes are the aldehyde-H wag, the CHO torsion and CHO wag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The lifetime of carbonyl triplet excited states in rigid media at low temperature has been found to be dependent upon isotopic substitution.31 The lifetime of benzaldehyde triplet in EPA at 77 K was found to depend upon isotopic substitution at the aldehyde carbon.32 Furthermore, spectroscopic investigation of benzaldehyde has revealed that the aldehydic hydrogen plays an important, if not dominant, role in the radiationless deactivation of the electronically excited triplet state. 33 The effect of deuterium substitution on the lifetime of triplet excited states has been attributed to the difference in the Franck-Condon overlap factors for the hydrogen and deuterium substituted compounds. 34 That is, at constant vibrational excitation energy, the deuterium substituted compound would be at a considerably higher vibrational quantum number than the hydrogen substituted compound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lifetime of carbonyl triplet excited states in rigid media at low temperature has been found to be dependent upon isotopic substitution.31 The lifetime of benzaldehyde triplet in EPA at 77 K was found to depend upon isotopic substitution at the aldehyde carbon.32 Furthermore, spectroscopic investigation of benzaldehyde has revealed that the aldehydic hydrogen plays an important, if not dominant, role in the radiationless deactivation of the electronically excited triplet state. 33 The effect of deuterium substitution on the lifetime of triplet excited states has been attributed to the difference in the Franck-Condon overlap factors for the hydrogen and deuterium substituted compounds. 34 That is, at constant vibrational excitation energy, the deuterium substituted compound would be at a considerably higher vibrational quantum number than the hydrogen substituted compound.…”
Section: Discussionmentioning
confidence: 99%
“…32 Furthermore, spectroscopic investigation of benzaldehyde has revealed that the aldehydic hydrogen plays an important , if not dominant, role in the radiati onless deactivation of the electronically exci ted triplet state. 33 These effects of deuteriuli substituti on have been attributed to the di fference in the spacing of the vibrational l evel s of the carbon-hydrogen and carbon deuterium bonds . 3• That is, at constant vibrational exci tation energy, the deuterium substi tuted compound would be at a considerably higher vibrational quantum number than the hydrogen substi tuted compound.…”
Section: -mentioning
confidence: 99%
“…[13] In contrast, the organic halides 2, the olefins 3, and 2,6-lutidine do not absorb within this frequency region. [17] The photochemistry of 1 a is dominated by reactions of the lowest electronically excited triplet state, [13] which possesses a relatively long lifetime [18] along with a triplet energy (E T ) of 300 kJ mol À1 . We did not detect any groundstate association between the reaction components by spectroscopic and absorption measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Detection of such photolysis products [16] suggests that 1 a can be capable of sensitizing the alkyl halides 2 to the excited triplet state upon illumination, thus inducing an n!s * transition which would result in a rapid homolytic dissociation of the CÀX bond in 2. [17] The photochemistry of 1 a is dominated by reactions of the lowest electronically excited triplet state, [13] which possesses a relatively long lifetime [18] along with a triplet energy (E T ) of 300 kJ mol À1 . This energetic value is in the range of the carbon-halogen bond dissociation energies of the alkyl halides used in this ATRA methodology (260-300 kJ mol À1 , see Table S1 in the Supporting Information), which is congruent with a homolytic cleavage of 2 induced by an energy-transfer mechanism.…”
Section: Methodsmentioning
confidence: 99%